Insulin-Like Growth Factor-Binding Proteins of Teleost Fishes - Garcia de la Serrana, Daniel; Macqueen, Daniel J. (Frontiers in Endocrinology, 2018)
The insulin-like growth factor (IGF) binding protein (IGFBP) family has a broad range of physiological functions and a fascinating evolutionary history. This review focuses on the IGFBPs of teleost fishes, where genome duplication events have diversified gene repertoire, function and physiological regulation - with six core IGFBPs expanded into a family of over twenty genes in some lineages. In addition to briefly summarizing the current state of knowledge on teleost IGFBP evolution, function and expression-level regulation, we highlight gaps in our understanding, and promising areas for future work.